FACTORS INFLUENCING THE IMPLEMENTATION OF THE MOBILE TEACHER PROGRAM IN INCREASING COLLECTIONS' WORK SPIRIT - Rohliyati, Rohliyati; Annur, Saipul; Zainuri, Ahmad; Saputra, Ade Akhmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze the influencing factors of the strategy for implementing School Operational Assistance (BOS) financing in overcoming distortions in financing communication for Prabumulih 3 Public Senior High School. This research is a qualitative research. In data collection, researchers used several collection techniques, namely: (1) in-depth interviews, (2) observation, (3) documentation study. The data analysis technique uses the analytical method using the Miles and Huberman Model which consists of three stages, namely: data reduction, data display, and drawing conclusions or verification. following: Support from the Central Government, Support from Local Government and Cooperation and communication between managers. While the inhibiting factors in the management of school operational assistance funds (BOS) are as follows; At the time of disbursement, the BOS funds could not be used for major repairs, and the BOS funds had not been able to finance all school programs.